Matching with Couples: a Multidisciplinary Survey - Péter Biró; Flip Klijn (Hungarian Academy of Sciences, Institute of Economics, 2011)
This survey deals with two-sided matching markets where one set of agents (workers/residents) has to be matched with another set of agents (firms/hospitals). We first give a short overview of a selection of classical results. Then, we review recent contributions to a complex and representative case of matching with complementarities, namely matching markets with couples. We discuss contributions from computer scientists, economists, and game theorists.
Keywords: 330; matching; couples; stability; computational complexity; incentive compatibility; restricted domains; large markets; Spieltheorie; Matching; Markt; Interdisziplinäre Forschung